2013
DOI: 10.1111/ceo.12259
|View full text |Cite
|
Sign up to set email alerts
|

Rise of intraocular pressure in a caffeine test versus the water drinking test in patients with glaucoma

Abstract: The rise in intraocular pressure was greater with water drinking test than the caffeine test. Caffeine does not appear to provide an alternative for patients unable to tolerate the water drinking test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…14 Similarly, Ulas et al have shown that IOP elevation after WDT in healthy eyes occurs within the first 10 minutes and recovers quickly. 19 Tran et al reported mean peak IOP was highest at 45 minutes after water ingestion in patients with primary open-angle glaucoma (POAG), 20 whereas Hatanaka et al found that mean peak IOP was highest at 30 minutes in subjects with ocular hypertension and open-angle glaucoma. 21 It has been postulated that a more rapid return to baseline IOP following WDT may reflect an improved outflow facility.…”
Section: Interpreting the Resultsmentioning
confidence: 99%
“…14 Similarly, Ulas et al have shown that IOP elevation after WDT in healthy eyes occurs within the first 10 minutes and recovers quickly. 19 Tran et al reported mean peak IOP was highest at 45 minutes after water ingestion in patients with primary open-angle glaucoma (POAG), 20 whereas Hatanaka et al found that mean peak IOP was highest at 30 minutes in subjects with ocular hypertension and open-angle glaucoma. 21 It has been postulated that a more rapid return to baseline IOP following WDT may reflect an improved outflow facility.…”
Section: Interpreting the Resultsmentioning
confidence: 99%
“…This is somewhat different from results with glaucomatous eyes. Tran et al reported mean peak IOP was highest at 45 min after water ingestion, whereas Hatanaka et al found that, on average, mean peak IOP was highest at 30 min, in a cohort of 88 eyes with ocular hypertension or primary open‐angle glaucoma (POAG).…”
Section: Interpreting Resultsmentioning
confidence: 99%
“…43 First, IOP peak results obtained through the WDT tend to systematically overestimate those observed during other IOP variation tests, such as diurnal tension curves, postural change test, and caffeine test. 28,44,45 This suggests that the water overload promoted during the WDT could lead to a non-physiological IOP rise. Second, WDT results can be influenced by factors not related to glaucoma, such as patient body mass index and use of systemic antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%